Major fragment of soluble peptidoglycan released from growing Bordetella pertussis is tracheal cytotoxin. - Rosenthal, R S (1987)
Bordetella pertussis is known to release a factor which promotes the loss of ciliated respiratory epithelium and copurifies with a soluble peptidoglycan (PG) fragment termed tracheal cytotoxin (TCT). The objective of this study was to determine whether pertussis organisms turn over and release PG derivatives in addition to TCT. B. pertussis Tohama (phase III) was grown in liquid Stainer-Scholte medium containing [3H]diaminopimelic acid (DAP) to label PG specifically, washed to remove free label, and suspended in fresh medium without [3H]DAP. Molecular sieve chromatography of supernatants obtained from such cultures revealed a single included peak of 3H, the elution volume of which corresponded roughly to a disaccharide peptide monomer standard (ca. 10(3) daltons). This material (i) contained [3H]DAP in acid-hydrolyzable linkage, (ii) comigrated with 1,6-anhydro-N-acetylmuramic acid-containing disaccharide peptides on paper chromatography, (iii) was resistant to degradation by mild alkali, and (iv) was indistinguishable from authentic TCT by high-voltage paper electrophoresis and two reversed-phase high-performance liquid chromatography systems. Together, the data suggest that B. pertussis releases a markedly homogeneous set of PG fragments, consisting principally of TCT, and that TCT is possibly a nonreducing, anhydromuramic acid-containing fragment or a cyclic PG derivative.